Exome-First Approach in Fetal Akinesia Reveals Chromosome 1p36 Deletion Syndrome. (2nd October 2019) - Toshimitsu, Masatake; Nagaoka, Shinichi; Kobori, Shuusaku; Ogawa, Maki; Suzuki, Fumihiko; Kato, Takema; Miyai, Shunsuke; Kawamura, Rie; Inagaki, Hidehito; Kurahashi, Hiroki; Murotsuki, Jun
Abstract : Background . Fetal akinesia refers to a broad spectrum of disorders with reduced or absent fetal movements. There is no established approach for prenatal diagnosis of the cause of fetal akinesia. Chromosome 1p36 deletion syndrome is the most common subtelomeric terminal deletion syndrome, recognized postnatally from typical craniofacial features. However, the influence of chromosome 1p36 deletion on fetal movements remains unknown. Case Report . A 32-week-old fetus with akinesia showed multiple abnormalities, including fetal growth restriction, congenital cardiac defects, and ventriculomegaly. G-banding analysis using cultured amniocytes revealed 46, XY, 22pstk+. Postnatal whole exome sequencing and subsequent chromosomal microarray identified a 3 Mb deletion of chromosomal region 1p36.33–p36.32. These results of molecular cytogenetic analyses were consistent with the fetal sonographic findings. Conclusion . Using the exome-first approach, we identified a case with fetal akinesia associated with chromosome 1p36 deletion. Chromosome 1p36 deletion syndrome may be considered for differential diagnosis in cases of fetal akinesia with multiple abnormalities.